Acoustical behavior of hybrid composite sandwich panels - Patinha, Sérgio (2015)
This paper deals with the characterization of acoustic insulation behaviour of hybrid sandwich composite panels for application in modular house construction. These sandwich panels are a sustainable, light-weight and durable solution, since are based on natural fibers structure impregnated with a thermosetting polymer. In this way, three different types of hybrid composite panels containing polyurethane core and laminated composite skins were produced and analyzed, varying the composition of laminates. The composite laminates of the prototypes were produced using a vacuum infusion technique and were composed of glass and jute fibers, impregnated with a polyester resin. The solutions developed were compared with a standard, composed of plasterboards having different thicknesses and used for thermal and acoustic insulation. Acoustic insulation characterization was performed on specimens with 220x220 mm size in a sound proof acoustic chamber. The tested sandwich panels showed promising results; however, their overall performance was lower as compared to the performance of standard solutions used for comparison. Nevertheless, the specific acoustic insulation performance, i.e. sound reduction per unit mass of material for the developed sandwich panels was significantly higher as compared to the standard materials, indicating better suitability of this innovative solution for light-weight construction and modular housing.